Forces and Theories Underlying Management Response in Business Reporting for Improved Sustainability Disclosure - Capener, Elizabeth D.; Bullen, Maria L.; Kordecki, Gregory S. (Journal of Applied Business and Economics, 2017)
Management response to catastrophic events can vary significantly from stated company policy on environmental reporting. This paper explores management’s response under two theories: (1) as an aspect of legitimacy, adapting activity to changing perceptions, and (2) as an aspect of stakeholder interest, looking to the needs of several groups. The paper concludes that forces beyond the general social, legal, and accounting are required to develop appropriate disclosure, and argues for increased ethical and governance force in establishing disclosure helpful to standard setters, regulators, auditors, the general public, and all users of company financial and non-financial information.